The Probe Team [episode no. 274] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
A Victory for Justice is an interview of four accused members on Lenny Villa case of an Ateneo de Manila University fraternity. A study conducted on the Metro Manila youth who grew up detatched from their parent is presented in Generation X. Japina is a cultural center stage play portraying the Japanese exploitation from comfort women though the present day Japayuki.
A Victory for justice (17 min.) -- Generation X (13 min.) -- Japina (20 min.)
Keywords: Initiations (into trade, societies, etc.).; Greek letter societies -- Quezon City; Custody of children -- Manila Metropolitan Area; Youth -- Manila Metropolitan Area; Women -- Crimes against. -- Philippines; Women -- Social conditions. -- Philippines; Prostitution